2017
DOI: 10.1108/nfs-07-2016-0098
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and antinutrient composition of improved sweet potato [Ipomea batatas (L) Lam] varieties grown in eastern Ethiopia

Abstract: Purpose The purpose of this study was to compare the nutrient and antinutrient content of two improved sweet potato varieties released for drought prone areas of eastern Ethiopia. Design/methodology/approach Matured roots of two sweet potato varieties, namely, Berkume and Adu, were collected from Haramaya University, Toni Research Farm, Ethiopia. The sweet potatoes were ground into flour following standard procedure. Thereafter, proximate, dietary minerals and β-carotene were determined by official methods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
3
10
1
3
Order By: Relevance
“…As far as crude fiber content, values varied from 0.89±0.09 to 2.92±0.16 % for the white (WSPF-WC) and yellow fleshed cultivars (YSPF-WC), respectively. These values are similar to those reported in previous studies for other sweet potato roots cultivated in Benin and Ethiopia, respectively ( Sanoussi et al, 2016;Mitiku &Teka, 2017). Nevertheless, the values are lower compared to those obtained by Kim et al (2011) and Nicanuru et al (2015), this indicate that these sweet potato cultivars are poor sources of dietary fiber.…”
Section: Nutritive Va Lue Of the Sweet Potato Flourssupporting
confidence: 91%
See 1 more Smart Citation
“…As far as crude fiber content, values varied from 0.89±0.09 to 2.92±0.16 % for the white (WSPF-WC) and yellow fleshed cultivars (YSPF-WC), respectively. These values are similar to those reported in previous studies for other sweet potato roots cultivated in Benin and Ethiopia, respectively ( Sanoussi et al, 2016;Mitiku &Teka, 2017). Nevertheless, the values are lower compared to those obtained by Kim et al (2011) and Nicanuru et al (2015), this indicate that these sweet potato cultivars are poor sources of dietary fiber.…”
Section: Nutritive Va Lue Of the Sweet Potato Flourssupporting
confidence: 91%
“…Moisture contents of the selected sweet potato flours was in the range of 4.50±0.10 to 6.30±0.15%. This range of moisture is reasonably comparable to the moisture content reported for others sweet potato flour of Nigeria and Ethiopia (Ohizua et al, 2016;Mitiku & Teka, 2017). The low moisture value (lower than 10%) obtained in this study agreed with the range of moisture generally accepted as standard value for dry products with a long self-life (Sriroth, Piyachomkwan, Wanlapatit, & Oaste, 2000).…”
Section: Nutritive Va Lue Of the Sweet Potato Flourssupporting
confidence: 90%
“…It is significantly influenced by these different effects at different thresholds. Carbohydrate synthesis is influenced by crop treatment, soil type and climatic conditions at the growing site [26]. Just like carbohydrates, fibers are also influenced by the same factors as earlier mentioned.…”
Section: Discussionmentioning
confidence: 80%
“…It should be noted that the water levels obtained (<14%) are favourable for good conservation in tropical areas over a long period of time [25]. The ash content represents the inorganic matter of the plant, particularly ions [26]. Concerning this parameter, it is found that it is significantly (p<0.05, 0.01, 0.001) influenced variety, blanching and combination between these two effects.…”
Section: Discussionmentioning
confidence: 99%
“…While it may be cheaper to produce fuel ethanol from whole FA tubers, the issue of phytochemicals (or antinutrients) becomes a factor for consideration. Similar to other tuber or root crops, such as, sweet potato (Mitiku and Teka, 2017), yam (Shajeela et al, 2011), and cassava (Shajeela et al, 2011), FA tubers were also rich in antinutrients (Table 10). Since details about the antinutrient contents of FA starch are less clear, this suggests that future research should explore the antinutrient contents of FA starch as well as the elemental contents.…”
Section: Fa For Fuel Grade Ethanol Production Programme In Nigeriamentioning
confidence: 92%